Unpacking uncivil society - Oh Dayei; Elayan Suzanne; Sykora Martin; Downey John (Nordicom Review)
In the era of rising populist sentiment, deep social and political polarisations, and a growing crisis of online harms, numerous scholars share concern about the impact of such uncivil populist forces on the health of liberal democracy. This article argues that we should first normatively distinguish between incivility and intolerance. We contend that the core problem of uncivil society is intolerance, not incivility. We then empirically analyse incivility and intolerance during the 2018 Irish abortion referendum and its discussions on Twitter by conducting a content analysis and qualitative textual analysis of 3,000 tweets posted between April and June 2018. The results show that despite selecting a highly emotive and polarised issue, incivility and intolerance do not dominate the Twittersphere. Furthermore, gender and political position of users were found to be associated with use of incivility and intolerance, which increased as the referendum approached.